IMPROVEMENT OF SOLID WASTE MANAGEMENT: ORGANIZATIONAL AND TECHNOLOGICAL ASPECTS - Minakova, Irina; Bukreeva, Tatyana Bukreeva; Timofeeva, Olga (Journal of Applied Engineering Science, 2018)
The paper reveals the existing problems in of solid domestic waste recycling in the developed western countries and in Russia. A direct pattern is shown: the more country developed, the more waste it processes (later wastes are reused) and composts. It is established that the existing system of solid domestic waste circulation in Russia is based on their collection and transporting for disposal in landfills and dumps. Using ineffective ways of residential solid waste disposal leads to a rapid filling of landfills, even in spite of small volumes of incoming wastes and significant areas allocated for their disposal. Taking into account the specifics of a curtain territory, the structural and technological recommendations for improving residential solid waste management in the regionbased on of the method of complex processing of residential solid waste are proposed.